GRADIENT REMEDIABILITY IN LINEAR DISTRIBUTED PARABOLIC SYSTEMS ANALYSIS, APPROXIMATIONS AND SIMULATIONS - Rekkab, S.; Benhadid, S. (University of Eloued جامعة الوادي, 2017)
The aim of this paper is the introduction of a new concept that concerned the analysis of a large class of distributed parabolic systems. It is the general concept of gradient remediability. More precisely, we study with respect to the gradient observation, the existence of an input operator (gradient efficient actuators) ensuring the compensation of known or unknown disturbances acting on the considered system. Then, we introduce and we characterize the notions of exact and weak gradient remediability and their relationship with the notions of exact and weak gradient controllability. Main properties concerning the notion of gradient efficient actuators are considered. The minimum energy problem is studies, and we show how to find the optimal control which compensates the disturbance of the system. Approximations and numerical simulations are also presented. Â
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: actuators efficient; disturbance; gradient; parabolic systems; remediability; sensors.